2019
DOI: 10.1186/s40425-018-0459-y
|View full text |Cite
|
Sign up to set email alerts
|

Avelumab in patients with previously treated metastatic melanoma: phase 1b results from the JAVELIN Solid Tumor trial

Abstract: BackgroundWe report phase 1b data from patients enrolled in the JAVELIN Solid Tumor clinical trial (NCT01772004) with unresectable stage IIIC or IV melanoma that had progressed after ≥1 line of therapy for metastatic disease.Patients and methodsPatients received avelumab (10 mg/kg)—a human anti–PD-L1 antibody. Assessments included objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and safety.ResultsAs of December 31, 2016, 51 patients were treated and followed for a median o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…Heterogeneity: I 2 = 92%, τ 2 = 0.5527, p < 0.01 Rittmeyer et al [79] Fehrenbacher et al [87] Powles et al [81] Barlesi et al [97] Bang et al [121] Peters et al [80] Petrylak et al [82] Colevas et al [86] Horn et al [85] Lukas et al [84] Spigel et al [83] McDermott et al [77] Gulley et al [90] Dirix et al [93] Chung et al [102] Disis et al [101] Kelly et al [95] Keilholz et al [100] Hassan et al [99] Le et al [98] Antonia et al [104] Yang et al [107] Massard et al [103] Segal et al [111] Zandberg et al [110] Siu et al [109] Herbst et al [76] Garassino et al […”
Section: Fixed Effect Model Random Effects Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterogeneity: I 2 = 92%, τ 2 = 0.5527, p < 0.01 Rittmeyer et al [79] Fehrenbacher et al [87] Powles et al [81] Barlesi et al [97] Bang et al [121] Peters et al [80] Petrylak et al [82] Colevas et al [86] Horn et al [85] Lukas et al [84] Spigel et al [83] McDermott et al [77] Gulley et al [90] Dirix et al [93] Chung et al [102] Disis et al [101] Kelly et al [95] Keilholz et al [100] Hassan et al [99] Le et al [98] Antonia et al [104] Yang et al [107] Massard et al [103] Segal et al [111] Zandberg et al [110] Siu et al [109] Herbst et al [76] Garassino et al […”
Section: Fixed Effect Model Random Effects Modelmentioning
confidence: 99%
“…This analysis compared 11 different ICI-related (grade 1-5 and 3-5) AEs, including a total of 147 studies and 23 761 patients. The interventions were: 46 pembrolizumab articles (n = 6598), 27 nivolumab articles (n = 3576), 13 atezolizumab articles (n = 2787), [76][77][78][79][80][81][82][83][84][85][86][87][88] 12 avelumab articles (n = 3213), [89][90][91][92][93][94][95][96][97][98][99][100][101][102] 10 durvalumab articles (n = 1780), [103][104][105][106][107][108][109][110][111] 22 ipilimumab articles (n = 4067) 5, ; eight tremelimumab articles (n = 1158), [133][134][135][136][137][138][139][140] three JS001 articles (n = 223), [141][142]…”
Section: Basic Characteristics Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…10 11 In previous clinical trials, avelumab has demonstrated clinical activity and a tolerable safety profile in patients with various other tumor types, including platinum-treated NSCLC. [12][13][14][15][16] Here, we report efficacy and safety data from a phase I expansion cohort of the JAVELIN Solid Tumor trial in which patients with advanced NSCLC received first-line avelumab. Preliminary findings from this cohort led to the initiation of the phase III JAVELIN Lung 100 study (NCT02576574) of first-line avelumab versus platinum-based doublet chemotherapy in patients with PD-L1-positive NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…In 9 May 2017, the FDA granted accelerated approval to avelumab for patients with locally advanced or metastatic urothelial carcinoma whose disease progressed during or following platinum-containing chemotherapy or within 12 months of neoadjuvant or adjuvant platinum-containing chemotherapy based on the JAVELIN Solid Tumor trial [75] (Category 2A, alternative to preferred agent pembrolizumab, which is category 1). On 14 May 2019, the FDA approved avelumab in combination with axitinib (Inlyta) for the first-line treatment of patients with advanced RCC and it is the first FDA approval for an anti-PD-L1 therapy as part of a combination regimen for patients with advanced RCC.…”
mentioning
confidence: 99%